ProTru: a provenance-based trust architecture for wireless sensor networks - Dogan, Gulustan (WILEY, 2016)
Trust is an important component of wireless sensor networks for believability of the produced data, and trust history is a crucial asset in deciding trust of the data. In this paper, we show how provenance can be used for registering previous trust records and other information such as node type, data type, and node location. Our aim is to design a distributed trust-enhancing architecture using only local provenance during sensor fusion with a low communication overhead. Our network is cognitive in the sense that our system reacts automatically upon detecting low trust. Copyright (c) 2016 John Wiley & Sons, Ltd.
Keywords: FAULT-TOLERANCE; AD HOC; MODEL; Computer Science; Telecommunications